Tourism in Holy Cities and its impact on Economies Activity – kadimya AsExmp - جعفر عبد الحسن هاشم (Al-Adab Journal, 2018)
Tourism has become a contemporary civilized phenomenon which attracts the attention whether by the individuals or the governments, it helps to provide a good work income opportunities and it contributes in distributing development facilities across the country, which means raising the constructional and cultural level. Tourism development gains a special importance especially through the flow of the investment of foreign turnovers in tourism projects and through the scientific uses of the natural resources. The aim of this research is to shed the light upon several concepts including the concept of tourism and the essence of the religious tourism and its importance as well as the concepts of the holy cities or the cities of shrines, and the essence of tourism development and its impact to increase tourism spending amount in addition to the concept of tourism service which provides the tourist with comfort and touring facilities and other concepts which fall within the context of the research. In the practical side of the research and to reach its aims, the city of al-Kadimiya is tackled as a sample of the religious holy cities, where the city in many restaurants and hotels and their numbers if visitors and the total achieved income of the tourism activity during the period from 2004 to 2013 through the repeated revisions to a number of governmental and semi-governmental institutes, the sample of multiple falling is also used to achieve to verify the research hypothesis and finding the main factors which affect to increase the earned income of the religious tourism in the holy city of al-Kadymiya. The results of the statistical analysis show that all the visitors contribute to achieve income out of the religious tourism. At the end of the research many conclusions and recommendations we are research benefit, God speed.